ESTABLISHING A CONTACT WITH THE CHILD IN THE SOCIO-PSYCHOLOGICAL REHABILITATION CENTER (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
The article deals with the defining the content of contact process and contact with the child during one's placing and adaptation in the rehabilitation center. The author analyses some basic approaches of contact establishing with a child and distinguished its relevant features. Filonova's method of contact interaction is regarded as a way of establishing an effective communication and interaction with children and adolescents, especially with those who have a complex behavioral manifestations (deviant behavior, etc.). The author suggests special procedure of contact establishing with the children who, due to the difficult life circumstances, were placed to the Socio-psychological rehabilitation Center.The author states, that such contact should be based on supporting children in a new social situation to assist them to feel safe and secure.Thus, the fundamentals of the contact establishing are: positive emotional background, security situation creation, unconditional acceptance, confidence. The author convinced that the major responsibility for the trusting relationship formation between the child and employees of the Center lies on a psychologist. Establishing contact with the child and forming a trusting relationships provides favourable conditions for the feeling of secure and guarantees safety of child's emotional reactions, caused by their traumatic experience.Caregivers in the Center are responsible for children's physical and social development and learning skills, relevant to their age. Social care teacher (social worker) of the Center works with parents or trustees, in order to define causes and circumstances of the family life-crisis due to find out ways of overcoming and which are planned measures together with family to restore its functions, including the function of parenting.
Keywords: difficult life circumstances, contact, contact establishing, children, socio-psychological rehabilitation.